Ladder-like energy-relaying exciplex enables 100% internal quantum efficiency of white TADF-based diodes in a single emissive layer - Chunmiao Han (Nature Portfolio, 2021)
Realizing efficient white organic light-emitting diodes (WOLEDs) with a single thermally-activated delayed fluorescence (TADF) emissive layer remains a challenge. Here, the authors design energy-relaying exciplex hosts with multi-triplet excited states for efficient single-emissive-layer TADF WOLEDs.